Performance Enhancement of Field Oriented Induction Motor Drive System - Khurram, Adil (2016)
A Master of Science thesis in Electrical Engineering by Adil Khurram entitled, "Performance Enhancement of Field Oriented Induction Motor Drive System," submitted in November 2016. Thesis advisors are Dr. Habibur Rehman and Dr. Shayok Mukhopadhyay. Soft and hard copy available.